ThetaHealing® and Health: A Therapeutic Approach - Pérez-Arenas, Luis Ulises; Roldán, Jessica Paola Plascencia; Reyes, Guadalupe Irazú Morales; Flores-Vargas, Gilberto; Gallardo-Luna, María de Jesús; Navarro-Olivos, Efraín; Padilla-Raygoza, Nicolás (Research Highlights in Disease and Health Research Vol. 9, 2023)
ThetaHealing® therapy is a healing process that focuses on identifying and changing limiting beliefs and thought patterns that may harm a person's life. The therapy uses meditation and visualization techniques to access the Theta brainwave state -a state of deep, relaxed consciousness-. In this state, the therapist can work with the patient to identify and transform negative thought patterns and replace them with positive ones that support emotional health and well-being. ThetaHealing® therapy can also treat physical and emotional ailments and improve relationships and personal growth. ThetaHealing® therapy is based on the idea that we can create our reality through our thoughts and beliefs. We may carry significant and positive changes in our physical, emotional, and spiritual well-being by changing our limiting beliefs and aligning our thoughts with what we wish to manifest.